SYARḤ KITĀB AL-ARBA’ĪN AL-NAWAWIYYAH ON YOUTUBE: A STUDY OF INDONESIAN MUSLIM SCHOLARS’ INTERPRETATIONS ON HADITH BID’AH - Nurul Ihsannudin (Fakultas Ushuluddin dan Pemikiran Islam, Universitas PTIQ Jakarta, 2025)
The development of technology and information that is taking place today has an impact on religious studies and da’wah activities. Everyone who has a device and internet network can easily access religious informations that are widely spread on various social media platforms, such as Youtube. Religious informations that can be found on Youtube include the study of the hadith bid’ah of Al-Arbaʿīn Al-Nawāwiyyah book. This study seeks to explore how Indonesian muslim scholars interpret the hadith bid’ah from the Al-Arbaʿīn Al-Nawāwiyyah found on Youtube and what the implications of these interpretations are. This qualitative research uses descriptive-analytical method and finds that bid’ah cannot be interpreted textually so as to exclude all new things. The results of the interpretation also contain criticism of groups that interpret bid'ah textually.